A Scientometric Analysis of Metaverse Research Literature in Scopus Databases - Ndumo, David; Kiragu, David; Shano, Mohamed (Journal of Research in Vocational Education, 2025)
In this attempt, the authors have highlighted the Metaverse Literature that appeared in the Scopus Database, from 2006-2024, 4224 papers were published and received a total of 43990 citations. Initially, the publication rate was less, but from 2021 Metaverse literature has accelerated in its publication highest number of papers were published in the year 2024 as it is been publishing but the highest number of citations were observed in the year 2022 with 18511 citations. Maximum papers were found in the year 2022, but whereas in the case of authorship pattern, three authored papers are more in number with 880, in which single-authored papers 626 and the rest 3596 papers are considered as multi-authored papers. Authors have used more than 1700 different Channels of Communication to publish their research output but the highest number of papers are been published in the Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics) with 122 (2.89%) papers. China is the leading country in publishing Metaverse literature with 919 (21.76%) papers, whereas India stands in the third position with 464 (10.98%) papers.